Contemporary India: Is it a secular state or an ethnic nation? - Hussain, Nazir and Bagh, Sartik (South Asian Journal of Socio- Political Studies)
India is known as the world$1 (Bs largest democracy with a diverse range of languages, culture and faiths. The country$1 (Bs constitution offers specific rights to minorities to protect their dignity. However, recent political developments and policies implemented by the Bharatiya Janta Party (BJP) have caused concern over India$1 (Bs democratic heritage and the protection of religious rights. The BJP$1 (Bs repeated election victories have resulted in the formation of new laws that are inconsistent with India$1 (Bs secular system, and favoritism towards a single religion, hindering the rights of religious minorities. This paper discusses the current developments in India that are contributing to the emergence of an ethnic-nationalist ideology and a form of governance that is dominated by the majority community, leading to discriminatory practices against the largest religious minority group, Muslims, and the Dalit community.- Reproduced s